Digital Trust and Personality Types among Employees in the Workplace - Marcial, Dave E.; Arcelo, Alfie Q.; Montemayor, Jade O.; Binarao, Steven M.; Launer, Markus A. (Silliman Journal, 2024)
This study explores the relationship between personality traits and digital trust in the workplace. It emphasizes that trust is crucial to employees' willingness to embrace technology. Digital trust is defined as individuals depending on technology to complete tasks due to positive characteristics and expectations of the technology's behavior. The study focuses on the Big Five Personality traits: extraversion, agreeableness, conscientiousness, neuroticism, and openness, which are significantly related to digital trust. The research was conducted online in 36 countries, resulting in a dataset of 2,998 respondents. The findings revealed that respondents predominantly exhibited moderate levels of extraversion, openness, and neuroticism. However, agreeableness and conscientiousness traits were less prevalent among the respondents. The study also identified significant relationships between digital trust levels and the personality traits of extraversion, agreeableness, conscientiousness, neuroticism, and openness. Specifically, employees with higher extraversion showed higher digital trust levels, while those with higher agreeableness demonstrated the lowest digital trust. Additionally, the research highlighted that digital trust significantly varied across different ICT components when grouped according to employees' personality types. This indicates that trust in specific ICT components depends on individual personality traits. In conclusion, the study revealed that employees in the workplace generally exhibited moderate extraversion, neuroticism, and openness personality traits. The digital trust level among employees also shows a moderate overall level. The Big Five Personality traits significantly influenced digital trust, and employees' trust levels differed based on their personality types. Moreover, the research indicated significant differences in digital trust across various ICT components, depending on personality types. Considering the impact of personality traits on digital trust, organizations can design targeted interventions to promote a technology-embracing culture and enhance technology adoption. Recognizing the significance of extraversion, agreeableness, conscientiousness, neuroticism, and openness in influencing digital trust, organizations may also consider personality assessment tools during recruitment and talent management processes.